MEMANFAATKAN MESIN PEMOTONG RUMPUT SEBAGAI ALAT BANTU UNTUK MEMOTONG RUMPUT PADA SAAT MELAKUKAN GOTONG ROYONG DESA BUTTU BAYU PANEI RAJA - Andreas Vensen Sihombing; Tomi Mikael Sinaga; Adrian Jonathan Marthin Silalahi; Dongan Sapa Memito Sihombing; Jhon Supriadi Purba (Abdi Jurnal Publikasi, 2025)
A lawn mower is a tool used to cut grass and make it easier for someone to cut grass quickly and look neat compared to other manual lawn mowers. Buttu Bayu Panei Raja Village, Dolok Pardamean District, Simalungun Regency, North Sumatra Province. This village is a place that has a lot of potential that can be developed both from abundant natural resources due to fertile soil and good human resources. However, the problem found in Buttu Bayu Panei Raja Village is the lack of cleanliness in the village, such as cleanliness on village roads caused by grass that has reached the village road which causes anyone who passes it to feel disturbed, especially for two-wheeled and four-wheeled drivers. Observations were made by checking the location of Gotong-royong in the hamlet 1 - hamlet 5 of Buttu Bayu Panei Raja Village. The activities carried out in Buttu Bayu Panei Raja Village, Dolok Pardamean District, Simalungun Regency were carried out in a structured manner starting from the preparation stage to the implementation of activities by involving the local community, KPPM students from Class 2021, HKBP Nommensen University, Pematangsiantar, and several village officials who took direct action.